Influence of backbone length and synthetic mutations on orientation of neurotensin fragments adsorbed onto a colloidal silver surface: SERS studies. (25th September 2012) - Proniewicz, Edyta; Pienpinijtham, Prompong; Ozaki, Yukihiro; Kim, Younkyoo; Proniewicz, Leonard M.
Abstract : Neurotensin (NT) is a naturally occurring neurotransmitter that mediates the metabotropic seven‐transmembrane G protein‐coupled receptors, namely NTR1s, richly expressed on tumor surface. Therefore, mutated active molecular fragments of NT that possess selective antagonist or weak agonist properties and the high affinity to NTR1 have attracted considerable interest for use in thrombus, inflammation, and imaging/treatment of tumors. In this work, SERS spectra of three N ‐terminal fragments of human NT (NT 1‐6, NT 1‐8, and NT 1‐11 ) and six specifically mutated C ‐terminal fragments of human NT, including NT 8‐13, [Dab 9 ]NT 8‐13, [Lys 8, Lys 9 ]NT 8‐13, [Lys 8 ‐(®)‐Lys 9 ]NT 8‐13, [Lys 9, Trp 11, Glu 12 ]NT 8‐13, and NT 9‐13, adsorbed onto nanometer‐sized colloidal silver particles in an aqueous solution at pH level of the solution 2 are presented. A comparison was made between the structures of the native and mutated fragments to determine how changes in peptide length and mutations of the structure influenced the NT adsorption properties. Based on the interpretation of the obtained data, we showed that all of the investigated NT fragments, excluding [Lys 9, Trp 11, Glu 12 ]NT 8‐13, tended to adsorb on the silver surface mainly through the L‐tyrosine residue and the carboxylate group. The Tyr ring lied more‐or‐less flat on the silver surface. The hydrogen atom from the phenol group dissociated upon binding. On the other hand, [Lys 9, Trp 11, Glu 12 ]NT 8‐13 bound to this substrate through the close to vertical co‐pyrrole ring of the indole ring (Trp 11 ) and –COO ‐ . Comparison of the presented data with those obtained earlier for NT allows to suggest that in the case of naturally occurring neurotensin, both Tyr residues together with the carboxylate group play crucial role in the binding to the nanometer‐sized colloidal silver particles. This geometry of binding forces the NT molecule to lay flat on the surface. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : The SERS spectra of N ‐terminal fragments of human NT (NT 1‐6, NT 1‐8, and NT 1‐11 ) and also its six specifically mutated C ‐terminal fragments: NT 8‐13, [Dab 9 ]NT 8‐13, [Lys 8, Lys 9 ]NT 8‐13, [Lys 8 ‐(®)‐Lys 9 ]NT 8‐13, [Lys 9, Trp 11, Glu 12 ]NT 8‐13, and NT 9‐13 adsorbed onto nanometer‐sized colloidal silver particles in an aqueous solution at pH level of the solution 2 are presented. A comparison was made between the structures of the native and mutated fragments to determine how changes in peptide length and mutations of the structure influenced the NT adsorption properties.